Analysis of panel data - Hsiao, Cheng, 1943- (New York, NY : Cambridge University Press, 2014)
"This book provides a comprehensive, coherent, and intuitive review of panel data methodologies that are useful for empirical analysis. Sub stantially revised from the second edition, it includes two new chapter s on modeling cross-sectionally dependent data and dynamic systems of e quations. Some of the more complicated concepts have been further strea mlined. Other new material includes correlated random coefficient model s, pseudo-panels, duration and count data models, quantile analysis, an d alternative approaches for controlling the impact of unobserved heter ogeneity in nonlinear panel data models"--
Machine generated contents note: 1. Introduction; 2. Homogeneity tes t for linear regression models (analysis of covariance); 3. Simple regr ession with variable intercepts; 4. Dynamic models with variable interc epts; 5. Simultaneous-equations models; 6. Variable-coefficient models; 7. Discrete data; 8. Truncated and censored data; 9. Cross-sectional d ependent panel data; 10. Dynamic system; 11. Incomplete panel data; 12. Miscellaneous topics; 13. A summary view.
Includes bibliographical references and index.
Keywords: Econometrics; Panel analysis; Analysis of variance